2019
DOI: 10.1002/jmri.26864
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Involvement in Duchenne Muscular Dystrophy (DMD): An MRI Study

Abstract: Background Duchenne muscular dystrophy (DMD) is characterized by progressive weakness and wasting of skeletal, cardiac, and respiratory muscles, with consequent cardiopulmonary failure as the main cause of death. Reliable outcome measures able to demonstrate specific trends over disease progression are essential. Purpose To investigate MRI as a noninvasive imaging modality to assess diaphragm impairment in DMD. In particular, we sought to correlate MRI measurement of diaphragm structure and function with pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…The symptoms of Duchenne muscular dystrophy typically onset in young males between the ages of 3 and 5 years, with initial symptoms including delay in motor function, abnormal stride, difficulty standing from a sitting position and maintaining balance ( Darras et al, 2015 ). As the disease worsens, it affects all striated muscles, including weakening of the diaphragm ( Khirani et al, 2014 ; Gudmundson et al, 2019 ; Pennati et al, 2019 ) and limb muscles ( McDonald et al, 1995 ; Wallace and McNally, 2009 ), and in later stages, the disease also affects the heart ( Buddhe et al, 2018 ; Mavrogeni et al, 2018 ; Meyers and Townsend, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of Duchenne muscular dystrophy typically onset in young males between the ages of 3 and 5 years, with initial symptoms including delay in motor function, abnormal stride, difficulty standing from a sitting position and maintaining balance ( Darras et al, 2015 ). As the disease worsens, it affects all striated muscles, including weakening of the diaphragm ( Khirani et al, 2014 ; Gudmundson et al, 2019 ; Pennati et al, 2019 ) and limb muscles ( McDonald et al, 1995 ; Wallace and McNally, 2009 ), and in later stages, the disease also affects the heart ( Buddhe et al, 2018 ; Mavrogeni et al, 2018 ; Meyers and Townsend, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…13,35 Thus, the diaphragm becomes weaker compared to the other inspiratory muscles. Pennati et al 37 previously suggested in DMD that during quiet breathing the ribcage muscles partially compensate the increased fat fraction of the diaphragm, quantified by MRI, by increasing ribcage volume variation, quantified by OEP, to retain tidal volume.…”
Section: Discussionmentioning
confidence: 99%
“…Cell and molecular therapies are emerging for DMD (e.g. Datta et al 2020), concurrent with improved non-invasive monitoring of patients' ion homeostatic indicators (Mankodi et al 2017;Bishop et al 2018;Gerhalter et al 2019;Ropars et al 2020;Meng et al 2020;Pennati et al 2020). Whether Na +overload in DMD patients indicates fiber swelling that "is likely osmotically relevant" and thus "may contribute to the progressive muscle degeneration" (Weber et al 2011(Weber et al ,2012 has been unclear.…”
Section: Addressing the Basis Of Chronic Na + -Overload Via P-l/d Modmentioning
confidence: 99%